Legal Review Regarding Guidance at the Special Child Guidance Institution (LPKA) - Hasibuan, Hamdi (Inspiring Law Journal, 2024)
Problems arise when density occurs in LPKA, as explained above, the era of globalization tends to have a negative impact on the younger generation, thus encouraging them to commit a crime. As a result of the rapid and rapid development of information technology, sooner or later it will renew human behavior and civilization globally, because information technology makes the world limitless. The guidance system at the Special Child Guidance Institution (LPKA) in accordance with the integration policy aims to provide holistic protection, education, and rehabilitation for children in conflict with the law. Ideally, children receive formal education equivalent to public schools as well as vocational skills training to prepare them to return to society with adequate provisions, in addition to the implementation of the Psychosocial Rehabilitation Program, this program includes individual and group counseling, therapy, and social activities aimed at improving the psychological and social conditions of children. So that children are encouraged to participate in various recreational and sports activities to develop social and physical skills and maintain their mental health. Furthermore, in order to maintain the ethics and morals of children in LPKA, Religious and Moral Guidance is important to do, this program provides religious education and moral guidance to shape the character of children so that they have a strong moral foundation. Through this integration policy, it is hoped that children can undergo guidance more effectively and can reintegrate well into society, reducing the possibility of them being involved in criminal acts again